Penyuluhan Pengelolaan Keuangan Ukm Pengusaha Kuliner Di Pantai Gading Kelurahan Tanjungkarang Kota Mataram - H, Busaini; Suprianto; Wahyunadi; Sagir, Junaidi; Yasin, Muaidy; Manan, Abdul; Fuadi, Helmi (Universitas Mataram, 2024)
Abstract: The purpose of this study was to determine mangrove governance, community participation as a mangrove rehabilitation effort, and the level of community participation as a mangrove rehabilitation effort. This study uses a qualitative descriptive method. Data collection techniques using interview guidelines and questionnaires. Data analysis used descriptive qualitative and scoring. Sources of informants are all members of the mangrove working group as many as 21 people. The results of the study found that the holder of authority in mangrove management was the working group at the location of the activity. The goal is efforts to impact climate change, sustainable economic use, and prevent abrasion. The pattern of division of labor is divided into two working groups. The implementation mechanism; coordinating and disseminating activities to local governments and community groups, preparing technical designs, and providing field assistance. Supervision is supervised by a supervisory team at the location of the activity. The person in charge is the executor. Payments are made simultaneously for planting activities, provision of seeds, provision of materials, and other activities. Communities have participated in mangrove rehabilitation efforts starting from planning, monitoring, site selection, land preparation, seed preparation, and planting to maintenance. The level of community participation is in the high category with an average value of 20.